Influence of shear direction on the buckling of CFRP composite perforated plate - Yidris, Noorfaizal; Osman, Iman Syahirah; Gires, Ezanee (Elsevier, 2022)
The shear buckling performance of CFRP composite perforated plates taking due account of the influence of the flexural anisotropy is examined in this paper using the finite element analysis procedure. Typical laminated composite lay-up causes many complexities but can easily be dealt with in the numerical simulations. The results from the finite element models are shown to agree favourably with the buckling curves from the independent simulations using finite strip method of analysis. Results in the paper clearly show that care should be taken seriously for the case of composite structural members having opening in their webs. Depending on the nature of the applied shear loading, openings, and varied symmetric angle ply laminates, the buckling behavior and capabilities have also been altered.